Survey on risk Factors and clinical symptoms of hydatiform-mole in pregnant women referred to Ayatollah Rouhani hospital in Babol: 2011-2017 - Mohammad Ranaei; Ali Kaviyani; Akramosadat Hosseini; Mina Galeshi; Shahla Yazdani (Mashhad University of Medical Sciences, 2020)
Introduction: Molar pregnancy is a type of abnormal pregnancy which is divided into complete and partial hydatiform mole. Its incidence varies in different countries and in different regions in every country. Its incidence is higher in Asia than elsewhere in the world, whereas occasionally its risk factors and clinical symptoms are different in various regions. Therefore, this study was performed with aim to evaluate the risk factors and clinical symptoms of hydatiform-mole in pregnant women referred to Ayatollah Rouhani hospital in Babol. Methods: This retrospective descriptive study was performed on all pregnant women of hydatiforme mole with histopathologic definite diagnosis referred to the educational-therapeutic center of Ayatollah Rouhani Hospital in Babol from 2011-2017. Patients' information including demographic and clinical profiles was provided in a checklist format. Data were analyzed by SPSS software (version 18) and Chi-square and one-way ANOVA tests. P<0.05 was considered statistically significant. Results: In this study during 2011-2017, there were 19145 pregnancies in Babol Rouhani hospital. According to the pathology report, 70 cases of molar pregnancy were recorded. There were 41 (58.6%) of partial hydatidiform mole and 28 (40%) of complete hydatidiform mole. Most patients with molar pregnancy were in the age range of 20-35 years. 31 patients (44.3%) had O blood group. The most common symptom of the patients was bleeding 43(61.4%). Conclusion: The incidence of molar pregnancy was high compared with other parts of the world and the prevalence of partial hydatidiform mol was higher than other studies. The risk factors for molar pregnancy were: history of molar pregnancy, and O positive blood group. The most common clinical manifestation of molar pregnancy was bleeding.